Statistical analyses of SEM-EDS results to predict the quantity of added quicklime in a treated clayey soil. (30th August 2020) - Moretti, Laura; Conficconi, Massimiliano; Natali, Stefano; D'Andrea, Antonio
Highlights: Four procedures to prepare specimens of treated soil for SEM analyses. ANalysis Of VAriance and Tukey's test to identify the best procedure. Measuring Ca content of specimens with different percentages of added quicklime. Studying correlation between added quicklime and Ca content after treatment. Identification of high variability of Ca content in the treated soil. Abstract: In the road construction sector, soil treatment is a method for increasing the strength and durability of fine soils that would otherwise be waste: the treatment with lime allows building embankments with clayey soils. However, in-situ and laboratory tests should be carried out to verify the correct addiction of lime during earthworks. This study deals with SEM-EDS analyses in order to identify the most reliable method to prepare specimens and obtain relationship between added quicklime and Calcium content after treatment. A natural clayey soil has been tested: more than one thousand values of Calcium content have been analyzed with statistical approach. The results from one-way and two-way ANalysis Of VAriance (ANOVA) and Tukey's test confirmed the usefulness of SEM-EDS analyses to verify quickly the quantity of added quicklime in treated soils. The most reliable method for specimen preparation consists of a sequence of procedures similar to those that occur in worksite. The high variability of Ca content in the natural soil did not allow definition of a linear reliable relationship between the added quicklime and the after-treatment Ca content. Therefore, further experimentation is on-going to define a method based on SEM-EDS analyses and valid for clays with non-uniform chemical composition.